Integrating Local Wisdom into Numeracy Literacy: An Analysis of Students’ Competence in the Number Domain in Sigi Regency, Indonesia - Hajerina, Hajerina; Napitupulu, Mery; Lefrida, Rita; Walanda, Richard Albert (Jurnal Pendidikan MIPA, 2025)
Numeracy literacy is one of the basic competencies that support students' success in academic and social life. This study aims to analyze the numeracy literacy skills of junior high school students in Sigi Regency, Central Sulawesi Province, Indonesia, particularly in the domain of numbers, based on local wisdom such as the traditional Souraja buildings and agricultural practices of the residents of Sigi Regency. The sample comprised 120 eighth-grade students from six public junior high schools in Sigi Regency, representing diverse geographical characteristics (mountainous, rural, and urban) and varying educational performance levels. They were selected through purposive sampling and the mixed methods approach with an Explanatory Sequential Design as the research methodology. Data were collected using a numeracy literacy test developed using the AKM framework and numeracy competence indicators from the Ministry of Education, Culture, Research, and Technology (2023).  The results showed that only 10% of pupils reached the "Proficient" level. Most of them (65%) are in the ‘Basic’ or ‘Requiring Special Intervention’ group.  This decline in results is due to traditional teaching methods that fail to connect the material to the students' local environment.  Teaching math has not fully utilized local knowledge, such as how to do business in traditional markets and how to farm. These results indicate the need to revise the approach to teaching mathematics in schools, with an emphasis on integrating local knowledge into learning, namely, developing teaching methods that link mathematical concepts to students' daily lives, so that they are more relevant and engaging for students. In addition, this locally-based approach is expected to improve students' numeracy understanding and skills, especially for those who are still at a basic level or need special intervention. The development of a more contextual curriculum based on students' real experiences can also enrich the learning process and encourage significant improvement in academic outcomes.    Keywords: numeracy literacy, number domain, local wisdom of sigi.